A CRITICAL APPROACH TO RACE AND GENDER REPRESENTATION IN ENGLISH CLASSICAL LITERATURE - Aru, Aday; Megawati, Fika (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study investigates how race and gender are represented in canonical and contemporary English literature, offering a lens into historical power structures and social identity. Method: Using a critical literary analysis approach, the study examines four key works—Othello, Jane Eyre, Wide Sargasso Sea, and Americanah. Each text is analyzed to explore narrative strategies, character constructions, and social implications related to race and gender.  Results: The study finds that early literature reinforced social hierarchies through stereotypical representations, while later works increasingly interrogate and deconstruct these power dynamics. Postcolonial and feminist reinterpretations reveal the limitations of the original texts and offer more inclusive perspectives.  Novelty: By combining historical and contemporary works, this research demonstrates how literary narratives have both perpetuated and challenged dominant ideologies. It highlights the critical shift towards intersectionality in recent literature.